Zakat for the Welfare of the People in Government Institutions Carrying out National Zakat Management in Sidoarjo - Stevia Isabel Qolsum; Masruchin Masruchin (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to find out the efforts of Zakat, Infaq and Shadaqah for the welfare of the community in the National Amil Zakat Agency (BAZNAS) of Sidoarjo Regency and to know the supporting and inhibitory factors and efforts made in zakat, infaq and shadaqah efforts for the welfare of the community in the National Amil Zakat Agency (BAZNAS) of Sidoarjo Regency This research uses qualitative type methods with the research approach used is a case study approach. Data collection techniques use observation, interviews and documentation. Data analysis used data reduction, data presentation, and verification The results of research can be concluded several things, among others: Zakat, infaq and shadaqah efforts for the welfare of the community in the National Amil Zakat Agency (BAZNAS) of Sidoarjo Regency, namely with various programs including: Sidoarjo Cerdas, Sidoarjo Peduli, Sidoarjo Sehat, Sidoarjo Makmur, Sidoarjo Taqwa and the Annual Program in the form of mass Circumcision and Ramadan Parcels and Factors supporting efforts that Carried out in the management of zakat, infaq and shadaqah for the welfare of the community in the National Amil Zakat Agency (BAZNAS) of Sidoarjo Regency, among others, from the role of the Central Government and the Government of Sidoarjo Regency, BAZNAS Sidoarjo Regency has various relationships. While inhibiting factors include the lack of public confidence to leave zakat in BAZNAS Sidoarjo Regency, Lack of quality human resources, Lack of support by community leaders or institutions in the village.